Investigating the Anatomy and Microstructure of the Dentato-rubro-thalamic and Subthalamo-ponto-cerebellar Tracts in Parkinson's Disease - Lipp, Ilona; Mole, Jilu Princy; Subramanian, Leena; Linden, David E. J.; Metzler-Baddeley, Claudia (Frontiers in Neurology, 2022)
Cerebellar-thalamic connections play a central role in deep brain stimulation-based treatment of tremor syndromes. Here, we used diffusion MRI tractography to delineate the main cerebellar peduncles as well as two main white matter tracts that connect the cerebellum with the thalamus, the dentato-rubro-thalamic tract (DRTT) and the subthalamo-ponto-cerebellar tract (SPCT). We first developed a reconstruction protocol in young healthy adults with high resolution diffusion imaging data and then demonstrate feasibility of transferring this protocol to clinical studies using standard diffusion MRI data from a cohort of Parkinson’s disease patients and their matched healthy controls. The tracts obtained closely corresponded to the previously described anatomical pathways and features of the DRTT and the SPCT. Second, we investigated the microstructure of these tracts with fractional anisotropy, radial diffusivity and hindrance modulated orientational anisotropy in patients with Parkinson’s disease (PD) and healthy controls. Reducing dimensionality of both the microstructural metrics and the investigated cerebellar and cerebellar-thalamic tracts using principal component analyses, we found global differences between PD patients and controls, suggestive of higher fractional anisotropy, lower radial diffusivity and higher hindrance modulated orientational anisotropy in the patients. However, separate analyses for each of the tracts did not yield any significant differences. Our findings contribute to the characterisation of the distinct anatomical connections between the cerebellum and the diencephalon. Microstructural differences between patients and controls in the cerebellar pathways suggest involvement of these structures in PD, complementing previous functional and diffusion imaging studies.